Full-length transcriptome reconstruction reveals a large diversity of RNA and protein isoforms in rat hippocampus - Xi Wang (Nature Portfolio, 2019)
It is challenging to characterize diverse transcript isoforms by short-read sequencing. Here the authors report full-length transcriptomes in rat hippocampus by hybrid-sequencing, predict isoform-specific translational status, and reconstruct open reading frames validated by mass spectrometry.